Hybridization of 2D MoS2 Nanoplatelets and PtAu Hybrid Nanoparticles for the SERS Enhancement of Methylene Blue. Issue 21 (7th October 2021) - Lin, Shusen; Mandavkar, Rutuja; Kulkarni, Rakesh; Pandit, Sanchaya; Burse, Shalmali; Habib, Md Ahasan; Kunwar, Sundar; Lee, Jihoon
Abstract: SERS is a powerful technique that can offer an extraordinary capacity in the enhancement of weak Raman vibration and identification of molecules at a low concentration. In this work, a versatile hybrid SERS platform is demonstrated by the hybridization of 2D MoS2 nanoplatelets and core–shell PtAu hybrid nanoparticles (HNPs) for the enhancement of Raman vibration of methylene blue (MB). The MB is mixed with the MoS2 nanoplatelets and applied on the uniquely developed PtAu core–shell HNPs and significantly improved SERS is achieved as compared to a general SERS. The PtAu core–shell HNPs can offer the core–shelled PtAu NP configuration along with the highly dense background Au NPs, which exhibit much enhanced distribution of localized surface plasmon resonance (LSPR) and hot spots. The MoS2 nanoplatelets are 2D layered transition metal dichalcogenide (TMD) semiconductors, which can offer an ample charge transfer to the MB. The hybrid SERS platform takes the advantages from both the electromagnetic mechanism (EM) and chemical mechanism (CM). The finite‐different time‐domain (FDTD) simulation demonstrates the enhanced local e‐field distributions and increased maximum local e‐field intensity of the core–shell PtAu HNPs and combination of 2D MoS2 nanoplatelets/core–shell PtAu HNPs. Abstract : A noble hybrid surface enhanced Raman spectroscopy (SERS) platform is demonstrated with the 2D MoS2 nanoplatelets and core–shell PtAu hybrid nanoparticles, and significantly improved SERS of methylene blue (MB) is demonstrated as compared to the general SERS. The hybrid SERS platform takes advantage of both electromagnetic mechanism (EM) and chemical mechanism (CM) along with the strongly enhanced hot spots and localized surface plasmon resonance by the core–shell PtAu NPs and abundant charge transfer by the MoS2 nanoplatelets.